Valuing crop diversity in biodiesel production plans. (15th December 2015) - Baglivi, Antonella; Fiorese, Giulia; Guariso, Giorgio; Uggè, Clara
Abstract: The problem of defining efficient and environmentally compatible short-term agricultural plans for biodiesel exploitation is dealt with in this paper with a multi-objective modelling framework. To optimally use local resources, the first phase of the plan consists in the analysis of land and climate features in order to evaluate which energy crop can be successfully grown. This phase is performed at local scale using GIS (geographic information system) data and software. The second phase consists in the formulation of a multi-objective mathematical programming problem. Using the land to be cultivated in each parcel with each crop as decision variables, we solve a three objectives problem: the maximization of the net energy produced, of the greenhouse gases avoided with respect to conventional fossil fuels and of the diversity of the energy crop mix. The last is quantitatively measured using a well-known biodiversity index, which allows to study the trade-off between a more varied crop mix and the other two objectives along the frontier of Pareto efficient solutions. The proposed methodology is applied to a region of Mato Grosso, Brazil, where biodiesel is produced from oleaginous crops. Highlights: We adopt a modelling framework to define efficient biodiesel exploitation plans. A method to select energy crops and measure the value of a certain diversity is presented. A multi-objective non-linear programming problem is formulated. The problem is solved for biodiesel production in Mato Grosso, Brazil.